Предмет: Алгебра,
автор: ГравитиМан
ООООЧЕНЬ НААААДОООО
а)(x+2)(x-2)-x (x-6)=0
б)3x (4+12x)-(6x-1)(6x+1)=11x
в)(x+7)(x-7)-(3x-1)(x+4)=4-2x^2
Ответы
Автор ответа:
0
x^2-4-x^2+6x=0
6x=4
x=2/3
12x+36x^2-36x^2+1=11x
x=-1
x^2-49-3x^2-12x+4+x-4+2x^2=0
-49=11x
x=-49/11
6x=4
x=2/3
12x+36x^2-36x^2+1=11x
x=-1
x^2-49-3x^2-12x+4+x-4+2x^2=0
-49=11x
x=-49/11
Похожие вопросы
Предмет: Другие предметы,
автор: maasevamarina
Предмет: Биология,
автор: mail012014
Предмет: Физика,
автор: vikakuksa54
Предмет: Математика,
автор: Аноним
Предмет: Геометрия,
автор: madalievk